DESIGN AND SIMULATION OF A TUNABLE BANDPASS FILTER USING VARACTOR DIODES FOR WIRELESS AND RADAR APPLICATIONS - Belen, Mehmet Ali; Mahouti, Peyman; Partal, Hakan Pasa; Demirel, Salih; Gunes, Filiz (YILDIZ TECHNICAL UNIV, 2015)
This article discusses the development of an electronically tunable filter capable of a wide frequency tuning range. Variation of bias (0-5V) changes the center frequency of the filter within 10% while achieving a 1-dB of typical insertion loss. The concept of tuning a filter's 3-dB bandwidth with voltage is demonstrated and the effect of the bandwidth tuning elements on the tunable filter performance is discussed. The designed filter has a simple structure and the characteristics of wide tuning range of 1800MHz to 2000MHz and low insertion loss of less than -1.20 dB. The tunable bandpass filter can be scaled to the commercial frequencies up to 2.5GHz, offering advantages for most ISM and cellular band applications.
Keywords: Bandpass filter; varactor; tunable filter; PASSBAND; Engineering